Upgrading and Repairing PCs - Mueller, Scott (Indianapolis, Ind. : USA Que, 2006)
Computer Repair, PC Hardware, Hardware Installation, PC Care
Keywords: Computer Science; Technology; Microcomputers -- Equipment and Supplies; Microcomputers -- Upgrading; Microcomputers -- Maintenance and Repair